Neuroprotective Effect of Taurine against Cell Death, Glial Changes, and Neuronal Loss in the Cerebellum of Rats Exposed to Chronic-Recurrent Neuroinflammation Induced by LPS - Samara P. Silva; Adriana M. Zago; Fabiano B. Carvalho; Lucas Germann; Gabriela de M. Colombo; Francine L. Rahmeier; Jessié M. Gutierres; Cristina R. Reschke; Margarete D. Bagatini; Charles E. Assmann; Marilda da C. Fernandes (Journal of Immunology Research)
The present study investigated the neuroprotective effect of taurine against the deleterious effects of chronic-recurrent neuroinflammation induced by LPS in the cerebellum of rats. Adult male Wistar rats were treated with taurine for 28 days. Taurine was administered at a dose of 30 or 100 mg/kg, by gavage. On days 7, 14, 21, and 28, the animals received LPS (250 μg/kg) intraperitoneally. The vehicle used was saline. The animals were divided into six groups: vehicle, taurine 30 mg/kg, taurine 100 mg/kg, LPS, LPS plus taurine 30 mg/kg, and LPS plus taurine 100 mg/kg. On day 29, the animals were euthanized, and the cerebellum was removed and prepared for immunofluorescence analysis using antibodies of GFAP, NeuN, CD11b, and cleaved caspase-3. LPS group showed a reduction in the immunoreactivity of GFAP in the arbor vitae and medullary center and of NeuN in the granular layer of the cerebellar cortex. LPS increased the immunoreactivity of CD11b in the arbor vitae and in the medullary center. Taurine protected against these effects induced by LPS in immunoreactivity of GFAP, NeuN, and CD11b, with the 100 mg/kg dose being the most effective. LPS induced an increase in the number of positive cleaved caspase-3 cells in the Purkinje cell layers, granular layer, arbor vitae, and medullary center. Taurine showed its antiapoptotic activity by reducing the cleaved caspase-3 cells in relation to the LPS group. Here, a potential neuroprotective role of taurine can be seen since this amino acid was effective in protecting the cerebellum of rats against cell death and changes in glial and neuronal cells in the face of chronic-recurrent neuroinflammation.